Specialized knowledge of the mathematics teacher when analyzing a sequence of addition of fractions - Meléndez-Cruz, Julián Andrés; Flores-Medrano, Eric; Hernández-Rebollar, Lidia Aurora (Uniciencia, 2023)
[Objective] This paper is intended to identify and characterize the specialized knowledge of three mathematics teachers through the analysis of a sequence of activities intended to teach the sum of fractions using Cuisenaire Rulers. [Methodology]. A qualitative study using an interpretative paradigm was designed, and an intervention with the teachers was carried out during five sessions. Semi-structured interviews, a sequence of activities and Cuisenaire Rulers presented digitally were used as instruments for information collection. A model of specialized knowledge of the mathematics teacher developed by Carrillo and collaborators was used to characterize knowledge. This model makes it possible to identify the knowledge used by teachers in the field of mathematics, and to organize, classify and characterize it. [Results] The results of the investigation show a predominance of some of the subdomains that make up the model; in particular, a greater influence of knowledge of the topics and characteristics of learning mathematics. [Conclusions] Insights obtained during the investigation show the importance of identifying the knowledge that teachers make use of when thinking about an educational process, since this knowledge could help other teachers to improve or reflect on their teaching and learning practices in mathematics – in this particular case, in the study of fractions.